Improved Linear Attacks on the Chinese Block Cipher Standard - 刘明洁 陈佳哲 (Journal of computer science and technology, 2014)
The block cipher used in the Chinese Wireless LAN Standard （WAPI）, SMS4, was recently renamed as SM4, and became the block cipher standard issued by the Chinese government. This paper gives a method for finding the linear approximations of SMS4. With this method, 19-round one-dimensional approximations are given, which are used to improve the previous linear cryptanalysis of SMS4. The 19-round approximations hold with bias 2-62.27; we use one of them to leverage a linear attack on 23-round SMS4. Our attack improves the previous 23-round attacks by reducing the time complexity. Furthermore, the data complexity of our attack is further improved by the multidimensional linear approach.